PUNCHING SHEAR RESISTANCE OF STEEL FIBRE REINFORCED SELF-COMPACTING CONCRETE ONE-WAY RIBBED SLAB (Jurnal Teknologi (Sciences & Engineering), 2025)
In the field of modern construction engineering, the steel fiber reinforced self-compacting concrete (SFRSCC) represents a significant advancement over conventional reinforcement methodologies, presenting a promising avenue for achieving economic and temporal efficiencies without sacrificing structural robustness. This study focuses on the use of SFRSCC in the context of one-way ribbed slabs, which are strategically chosen for optimal performance in scenarios requiring an appropriate compromise of architectural aesthetics and mechanical strength, particularly in structures with medium spans, strict height, and overall mass constraints. The study investigates the advantages of the inherent stiffness of ribbed slabs and the outstanding compaction capabilities of self-compacting concrete (SCC) using an in-depth method that involves material selection, mix design, sample preparation, and comprehensive testing. The empirical results of this work show a considerable increase in the load-bearing capacity and ductility of SFSCC slabs, which is an immediate consequence of the steel fibers' characteristic high tensile strength and crack mitigation capabilities. This investigation highlights the improved structural performance and durability of SFRSCC in one-way ribbed slab applications and provides substantial evidence for its broader utilization in a variety of structural engineering projects, signalling a paradigm change in the direction of more sustainable and effective construction techniques.